Thermal Response Characteristics of Concrete-Filled Steel Tube Columns with Flame Encapsulation Thickness - Yang Can; Zhang Zhaoqiang (E3S Web of Conferences, 2024)
In order to elucidate the influence of flame encapsulation thickness on the thermal response characteristics of concrete-filled steel tube columns in a fire environment, a study was conducted focusing on the primary control mechanism of heat radiation power from fire——the thickness of fire encapsulation. The thermal resistance effect at the interface between the steel tube and concrete, as well as the temperature rise characteristics of the flame, were comprehensively considered. A calculation method was established for the thermal response characteristics of concrete-filled steel tube columns under different flame encapsulation thickness conditions, providing support for the simulation of thermal response and temperature rise prediction of concrete-filled steel tube columns in fires. The results indicate that the flame emissivity and radiant heat power increase with the increase of flame encapsulation thickness. As the flame encapsulation thickness gradually increases, the growth trend of flame radiant power slows down. When the flame encapsulation thickness L < 1 m, the temperature rise rate of the concrete-filled steel tube column is significant. When the flame encapsulation thickness L ≥ 1 m, the temperature rise rate of the concrete-filled steel tube column tends towards a constant value.